Attitudes towards sexuality in older adults treated in the outpatient clinic of the Hospital Nacional Hipolito Unanue, september - december, 2021: Actitudes hacia la sexualidad en adultos mayores atendidos en la consulta externa del hospital Nacional Hipólito Unanue, setiembre – diciembre, 2021 - Idrugo-Jave, Hallder (2023)
Objective: To determine the sociodemographic and clinical characteristics associated with positive attitudes towards sexuality in older adults seen in the outpatient clinic of the Hipólito Unanue National Hospital from september to december, 2021. Methods: Cross-sectional analytical observational study, which included 227 adult patients over 60 years of age from the outpatient clinic of the HNHU geriatrics service attended by teleconsultation. Attitudes towards sexuality were measured by applying the Questionnaire of Attitudes towards Sexuality in Older Adults, dividing the result into positive and negative attitudes. Results: 86.3% of older adults have a positive attitude towards sexuality, the age of 60 to 79 years was presented in 73% of these patients, higher education was higher in the group with positive attitude (47%), 53.6% of the patients with a positive attitude reported having a current partner, having received educational talks increases the probability of a positive attitude towards sexuality by 3.12 times. In the bivariate analysis, there was a statistically significant association between age 60 to 79 years (RP: 1.31, 95%CI: 1.12-1.52, p<0.001), higher education (RP: 1.19, 95%CI: 1.08-1.31, p=0.001), having a current partner (RP: 1.32, 95%CI: 1.19-1.46, p<0.001), having received educational talks (RP: 1.13, 95%CI: 1.03-1.24, p=0.033). In the multivariate analysis, an association was found between having a current partner and a positive attitude towards sexuality (RPa: 1.177, 95%CI: 1.09-1.26, p<0.001). Conclusion: There is a high frequency of positive attitude towards sexuality in older adults, and having a current partner was an independent associated factor.